Learning style of FSKM students / Nor Ain Zainal - Zainal, Nor Ain (2009)
The contemporary practices in the education are very often idealized from the administrative and pedagogical perspective. However, when one looks deeply into the teaching practices of the lecturers, it is possible to infer that the majority of the lecturers are not aware of their students learning styles. The problems arise when lecturers are unaware of the importance to establish and identify learning styles, therefore, when such attitude persists unanticipated consequences are to be expected. Students learning styles have been ignored and have been somehow considered as an insignificant component in the learning process. The purpose of this study was to determine the type of learning style of FSKM students and to recommend teaching aids for FSKM students. Survey was used as a method for gathering these requirements. The questionnaire was adapted from Ray Barch Learning style preferences instrument and distributed to 50 FSKM students who were randomly selected. The result showed that FSKM students are visual learners and prefer visual based learning.